Parents–Children Relationship Related to Religious Freedom and the Concept of Parental Direction Consistent With Child Evolving Capacities - Savić, Vanja-Ivan (Religion and Children's Rights, 2025)
Abstract:In this article, the author analyses and elaborates parent–child relationship in relation to religious freedom by examining international legal documents (conventional law), which regulate interactions in the most important social structure of society—family. The author explains the international conventional framework, which deals with the rights of children and parents, with particular emphasises on the European Court of Human Rights and Article 9 of the European Convention on Human Rights ECHR. The author explains that secularisation of contemporary society seeks to limit religious presence in the public domain to the extent possible, including religious education of children, which again, is parental prerogative. It primarily focuses on religious education in public schools. Meanwhile, there is a constant need to invent mechanisms that protect children from unwanted and harmful influences, regardless of whether they are internal (from the family) or external (from the society) and therefore emphasises the role of the committee that oversees the implementation of the Convention on the Rights of the Child. However, the recommendations of the committee are more observational and do not provide concrete guidelines or solutions as to how specific requests have to be implemented, if given. The article provides some suggestions that would place the right of the child to religious belief in balance with other potential rights of a child that exist in other legal areas.Keywords: Children, Parents, Religious Freedom, Parental Direction, Religious Education, Children Evolving Capacities, Europe